2002
DOI: 10.1017/s0252921100030785
|View full text |Cite
|
Sign up to set email alerts
|

New Results from the REX Survey

Abstract: Abstract. The REX survey is an ongoing project aimed at the selection of new samples of QSOs and BL Lac objects. Spectroscopic identification of the ~1600 sources in the survey is in progress reaching, so far, about 40% of complete identification level. In this paper, the most recent results derived from the REX survey are briefly summarized. The REX Survey: Sampling the BL Lac PopulationThe main scientific goal of the REX survey is the selection of new samples of AGNs, like radio-loud QSOs and BL Lac objects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The picture is however far from clear: while surveys like the Deep X-ray Radio Blazar Survey (DXRBS; Perlman et al 1998;Padovani et al 2002;Giommi et al, 2002), the "sedentary" survey (Giommi et al 1999) and the ROSAT -All Sky Survey (RASS; Bade et al 1998;Beckmann et al 2003) found very low values of V e /V a for XBLs, other surveys like the Radio Emitting X-ray survey (REX; Caccianiga et al 1999, Caccianiga et al, 2002 did not find the same result, possibly indicating that the negative evolution in this class of objects is not so strong as was previously measured.…”
Section: Spectral Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The picture is however far from clear: while surveys like the Deep X-ray Radio Blazar Survey (DXRBS; Perlman et al 1998;Padovani et al 2002;Giommi et al, 2002), the "sedentary" survey (Giommi et al 1999) and the ROSAT -All Sky Survey (RASS; Bade et al 1998;Beckmann et al 2003) found very low values of V e /V a for XBLs, other surveys like the Radio Emitting X-ray survey (REX; Caccianiga et al 1999, Caccianiga et al, 2002 did not find the same result, possibly indicating that the negative evolution in this class of objects is not so strong as was previously measured.…”
Section: Spectral Indicesmentioning
confidence: 99%
“…Since BL Lacs are both radio-loud and X-ray-loud, surveys in these frequency bands discover them with high efficiency (e.g. the "1 Jansky" sample: Stickel et al, 1991; the Einstein Extended Medium-Sensitivity Survey (EMSS) sample: Morris et al, 1991;Rector et al, 2000; the Deep X-ray Radio Blazar Survey (DXRBS) sample: Perlman et al, 1998, Landt et al 2001; the ROSAT All Sky Survey (RASS) sample: Bade et al, 1998; the "sedentary" survey: Giommi, Menna & Send offprint requests to: Anna Wolter, anna@brera.mi.astro.it Padovani, 1999; the Radio Emitting X-ray (REX) survey sample: Caccianiga et al, 1999, Caccianiga et al, 2002. This splits BL Lacs into two empirical subclasses, namely radio-selected BL Lacs (RBLs) and X-ray-selected BL Lacs (XBLs).…”
Section: Introductionmentioning
confidence: 99%